The emigration of Spanish abroad (2002-2011): geodemographic dimensions and characteristics - Romero-Valiente, Juan Manuel (Iberoamerican Journal of Development Studies, 2018)
The aim of this work is extended the knowledge of the geo-demographic dimensions and characteristics of the emigration of Spanish abroad that takes place between 2002 and 2011. The principal sources used are the statistics of Spanish emigration that publishes the National Institute of Statistics of Spain, the statistics of Spanish immigration of the countries recipients and a survey about the situation of the Spanish abroad realized in 2012. The principal findings and conclusions of this work are: the magnitude of the flow is very superior to the one that the Spanish statistics indicate, concerning the double; the women, the young persons and born abroad have a singular leadership in this process; the principal areas of origin of emigres are both big urban Spanish agglomerations (Madrid and Barcelona); western Europe and Latin America are the principal areas of destination, emphasizing as area recipient the United Kingdom.
Keywords: emigration; Spanish; geodemography; migratory statistics; survey